PENGGANDAAN BASIS DI DALAM LINGKUP PEREKONOMIAN REGIONAL WILAYAH TAPAL KUDA DALAM PERIODE SEBELUM MAUPUN SETELAH PELAKSANAAN OTONOMI DAERAH - Supriyono, Agus; Rondhi, Muhammad; Kusmiati, Ati (Jurnal Sosial Ekonomi Pertanian, 2011)
Finding on research result is as follow: First; investment on economic sector of basis in sub- region of Madura Island, sub-region of Madura Gulf and also Kabupaten Sumenep as well as Sidoarjo, either in the period of before and after regional autonomy has relatively good role in encouraging development of regional economy, particularly in encouraging export sector to outer region. Second; investment on economic sector of basis in City of Surabaya, Pasuruan and Probolinggo either in the period of before and after regional autonomy has relatively good role in encouraging development of regional economy, particularly in encouraging the development of export sector to outer region. Third; investment on economic sector of basis in sub-region of Madura strait and also in Kabupaten Bangkalan, Sampang, Pemekasan, Pasuruan, Probolinggo, as well as Situbondo, either in the period of before and after regional autonomy had caused the increase of demand for production in the economic sector of non- basis. Key Words: regional economy, base multiplier, Horse Shoe area, before and after regional autonomy